Searching the sky. - Romero, J.J (IEEE spectrum)
The paper presents an image-recognition software for astronomy pictures brings professional and amateur astronomers together. Astrometry.net's search software begins its analysis by looking for the brightest stars in the image and then uses sets of four such stars to draw four-sided shapes that is called quads. Each quad is like a fingerprint for a particular part of the sky. Rather than trying to find a perfect match, the program looks at many possible matches in a database of more than a billion stars. For each matching quad, the computer compares surrounding stars in the image to those predicted by information in the database and reports a successful match only when the stars' positions correspond with little discrepancy.